Developing Local Content Policy in Pursuit of Sustainable Development Goals - Aaron Yaw Ahali (Vestnik MGIMO-Universiteta)
The Sustainable Development Goals (SDGs) constitute a set of ambitious steps adopted to transform our world. They comprehensively outline action plans for social inclusion, environmental sustainability, and economic development. Achieving the SDGs by 2030 requires an unusual combination of action and partnership between various governmental and non-governmental organizations, development partners, the private sector, and civil society. While decision-makers are responsible for prioritizing and implementing strategies to ensure the various strategies embedded in the SDGs come to fruition, the private sector and civil society also play leading roles in implementing national plans. Local content policies (LCPs) are strategic policy frameworks focusing on diversification and technologically-led transformation in resourcerich economies. They are generally expressed through laws compelling stakeholders to procure services, create jobs within the host nation, and transfer technology. This paper stipulates that LCPs must be linked to the SDGs as this will help resource-rich countries fully benefit from their natural resources.